Novel Cu(200)/Ti cathode for the enhancement of N2 selectivity in direct ammonia electrolysis: The controls of Cu cathode facet orientation - Ming-Han Tsai; Yaju Juang; Chi-Chang Hu; Shih-Hua Chen; Lap-Cuong Hua; Chihpin Huang (Electrochemistry Communications, 2024)
Direct electrochemical ammonia oxidation reaction (AOR) using NiCu-based anodes is effective in removing ammonia from wastewater. However, this type of anode frequently produces undesired byproducts NO3−. Here, we investigated three configurations of novel Cu/Ti cathodes (Cu(111)/Ti, Cu(200)/Ti, Cu(220)/Ti) coupled with Cu/Ni foam (Cu/NF) anode to enhance N2 selectivity (SN2) in a direct ammonia electrolysis cell. Cu(200)/Ti cathode improved SN2 from 35 % (bare Ti cathode) to 60 % and it achieved 10–15 % higher SN2 compared to Cu(111)/Ti and Cu(220)/Ti. The improvement of SN2 on Cu(200) facet was ascribed to the high nitrate electroreduction activity and its conversion to N2. In real wastewater, Cu/NF anode-Cu(200)/Ti cathode paired electrolysis system demonstrated its excellent capability of 88 % NH3 removal with 95 % SN2. Our electrolysis system was capable to maintain the residual NH3-N and the NO3-N below 8 mg L−1, meeting effluent discharge standards. Our findings highlighted the importance of the control of Cu cathode facet orientations for an efficient elimination of NO3– and improvement of N2 production during direct ammonia electrolysis.